Climate Change Acts: Origins, Dynamics, and Consequences. (21st October 2021) - Nash, Sarah L.; Torney, Diarmuid; Matti, Simon
ABSTRACT: Framework legislation on climate change is coming of age. Ever more nation states and sub-state entities are passing Climate Change Acts (CCAs) – framework legislation that lays down general principles and obligations for climate change policymaking – and a number of early adopters are updating or replacing their initial legislation. This provides an opportune moment to bring together and move forward the scholarship on CCAs, examining where they have come from (their origins), how they work in practice (their dynamics), and what impacts they are having on the world and how it is organized (their consequences). The contributions to this Special Issue analyse the CCAs of Sweden, Mexico, New Zealand, Australian subnational governments, the UK, Denmark, Scotland and Austria as well as an unsuccessful attempt to introduce a Belgian CCA. Collectively, they add a wealth of new perspectives to the growing scholarship, identifying policy insights that can inspire further scholarship and future policy endeavours that can learn from these cases. The Special Issue contributions demonstrate that a number of contextual factors and elements of parliamentary process are important for successful passing of CCAs and/or high levels of ambition in the legislation itself. They highlight both the dangers and potential of policy fragmentation as dynamics of CCAs and the potential role for advisory bodies to shape these dynamics. Finally, consequences are identified in changes in political culture, parliamentary debate and the emergence of specific policies.